PENERAPAN PERSONAL HYGIENE PADA PRAKTIK MENGOLAH MAKANAN KONTINENTAL KELAS DUA PROGRAM KEAHLIAN TATA BOGA DI SMK N 3 SOLOK - Widaswara, Juwitalia; Liswarty, Liswarty; Baidar, Baidar (Faculty of Tourism and Hospitality - Universitas Negeri Padang, 2015)
The purpose of this study iss to describe the factors causing students do not apply to the practices of personal hygiene, describe factor cause students do not aply to the practices of completeness work clothes. Type of study is a qualitative research. Object of research are all students of grade two culinary skills program amounting to 20 students. Sampling technique by means of snowball sampling. Technigues of collecting data trough observation, interviews and documentasi. Field data anakysis techniques that include the reducation, display, conclusions or verifikasi. The result of this study indicate that the cleanliness of hair, hands and nose are not awake while physical fitness has been applied. Hygiene hats, work clothes, apron during the practices of students using white and clean, pants and shoes for the practice of students using black and baggy pants while students do not wear a tie.Keyword: Aplication of personal hygiene